Law and Regulation of Commercial Mining of Minerals in Outer Space - Lee, Ricky. author. aut Link
XXXII, 372 p.
Keywords: This monograph addresses the legal and policy issues relating to the commercial exploitation of natural resources in outer space. It begins by establishing the economic necessity and technical feasibility of space mining today, an estimate of the financial commitments required, followed by a risk analysis of a commercial mining venture in space, identifying the economic and legal risks. This leads to the recognition that the legal risks must be minimised to enable such projects to be financed. This is followed by a discussion of the principles of international space law, particularly dealing with state responsibility and international liability, as well as some of the issues arising from space mining activities. Much detail is devoted to the analysis of the content of the common heritage of mankind doctrine. The monograph then attempts to balance such interests in creating a legal and policy compromise to create a new regulatory regime.